ANALISIS PENGARUH MARKETING COMMUNICATION, RELATIONSHIP MARKETING DAN MINAT BELI TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA TOKO DUNIA LAMPU ELEKTRIK PANGKALPINANG) - Ardiansyah; Shinta Lestari, Deara; Hasianda Tigor, Ryan (Jurnal Progresif Manajemen Bisnis, 2022)
The purpose of this research is to analyze the influence of Marketing Communication, Relationship Marketing and buying interest on purchasing decisions, either simultaneously or partially. This research was conducted from February 2022 to July 2022. The theory used in this research is management theory, Marketing Communication, relationship marketing, buying interest and consumer purchasing decisions. The method used in this study is descriptive with a quantitative approach with a view to finding the relationship between the independent variables (Marketing communication, Relationship marketing and buying interest) with the dependent variable (purchase decisions) using statistical formulas, while the statistical formula used to test the hypothesis is multiple linear regression analysis. The sample in this study was 90 people (respondents). The results of this study prove that: (1) Marketing Communication has no effect on purchasing decisions, (2) Relationship Marketing has an effect on purchasing decisions (3) Purchase intention has no effect on purchasing decisions.